المؤسسة المشتركة ودواعي مراقبة مجلس المنافسة لها - بن الضيف, محمد عدنان; مزغيش, عبير (مجلة الاقتصاديات المالية البنكية وإدارة الأعمال; No 04 (2017): مجلة الاقتصاديات المالية البنكية و إدارة الأعمال, 2018)
الملخص تعتبر المؤسسة المشتركة، إحدى أوجه وأطر تكوين تجميعات اقتصادية، فهي وسيلة مستحدثة لإبرام عمليات التجميع الاقتصادي وذلك متى ما أنشئت لتؤدي بصفة دائمة جميع وظائف مؤسسة اقتصادية مستقلة. وكأصل عام تعد المؤسسة المشتركة من الآليات المباحة والتي لا تحتاج إلى مراقبة إلا إذا تجاوزت القيمة القانونية بتحقيق حد يفوق 40% من المبيعات والمشتريات المنجزة في السوق، مما يؤدي الى عرقلة المنافسة وتقييدها، وهنا يتدخل مجلس المنافسة باعتباره سلطة ضبط السوق بمراقبة التجميعات الاقتصادية التابعة عن مؤسسة مشتركة، لإعادة التوازن في السوق والمحافظة على المنافسة فيه. كلمات مفتاحية : المؤسسة المشتركة، التجميعات الاقتصادية، مجلس المنافسة، المراقبة Abstract The common enterprise, economic groupings, they are a way for the conclusion of an updated economic assembly operations is considered that once created to lead a permanent basis all the functions of an independent economic institution. And as an asset in longer joint institution of mechanisms that do not require monitoring only if they exceed the legal value of achieving an end more than 40% of sales and purchases carried out in the market, leading to obstruction of competition and restriction, and here intervenes Competition Council as the authority of the market set the monitor of an institution Economic assemblies common, to restore balance in the market and the preservation of competition in it. Key words: The common enterprise, economic assemblies, the Competition Council, control